Contact fault characterisation of complex silicon solar cells: a guideline based on current voltage characteristics and luminescence imaging. (23rd October 2015) - Padilla, Milan; Reichel, Christian; Hagedorn, Nikolaus; Fell, Andreas; Keding, Roman; Michl, Bernhard; Kasemann, Martin; Warta, Wilhelm; Schubert, Martin C.
Abstract: Highest efficiency solar cells in industrial and R&D environments are increasingly sensitive to local performance limiting processing faults, which are best characterised by spatially resolved characterisation techniques. This work contains a discussion on the processing faults related to contact resistance and finger interruptions in interdigitated back contact silicon solar cells, which are prime example for a complex cell structure. Using experimental and simulated current–voltage measurements and luminescence images, we explore the strongly non‐linear effect of poor local contact resistances on the global series resistance, fill factor, short circuit current density and efficiency. A good agreement between global and spatially resolved characterisation of faults is found, and potential artefacts are discussed. In conclusion, we present seven cases of contacting faults in interdigitated back contact cells with distinct characteristics that can be identified using a flow chart of experiments. The resulting guideline should assist silicon solar cell manufacturers in localising and quantifying local contacting faults that reduce the cells efficiency in manufacturing of complex solar cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work presents current‐voltage and luminescence characteristics of typical contacting faults in IBC silicon solar cells. Through numerical device simulations and experiments on especially fabricated and practical examples, we explore the strongly nonlinear effect of poor local contact resistances and interrupted fingers on global FF, JSC, Rs and efficiency. We present 7 cases of contacting faults and provide simple top‐down and bottom‐up guidelines for experimental identification in industrial production.